Impact Green Human Resource Management Towards Environmental Performance - Ahmad, Mauledy; Ali, Hapzi; Widyastuti, Tri; Suroso, Sugeng (Greenation Research & Yayasan Global Resarch National, 2024)
Research examining the impact of GHRM on environmental performance is essential to understand the relationship between GHRM and environmental performance. This study is interesting because it provides a comprehensive picture of the importance of the role of GHRM in improving environmental performance. The purpose of this study is to analyze various studies that have been conducted in the past to better understand the impact of GHRM on environmental performance through a systematic literature review. The success of GHRM in an organization is essential to optimize effectiveness, efficiency and competitiveness in facing tough global issues. Therefore, understanding the impact of GHRM on environmental performance will help design the right strategy to maintain sustainable environmental sustainability. The study is also relevant to rapidly growing trends, such as the issue of global warming and environmental damage that are paralyzing various aspects of life and business.